Exacerbation of the 2013–2016 Pan‐Caribbean Drought by Anthropogenic Warming. Issue 19 (7th October 2018) - Herrera, Dimitris A.; Ault, Toby R.; Fasullo, John T.; Coats, Sloan J.; Carrillo, Carlos M.; Cook, Benjamin I.; Williams, A. Park
Abstract: The Caribbean islands are expected to see more frequent and severe droughts from reduced precipitation and increased evaporative demand due to anthropogenic climate change. Between 2013 and 2016, the Caribbean experienced a widespread drought due in part to El Niño in 2015–2016, but it is unknown whether its severity was exacerbated by anthropogenic warming. This work examines the role of recent warming on this drought, using a recently developed high‐resolution self‐calibrating Palmer Drought Severity Index data set. The resulting analysis suggest that anthropogenic warming accounted for 15–17% of the drought's severity and 7% of its spatial extent. These findings strongly suggest that climate model projected anthropogenic drying in the Caribbean is already underway, with major implications for the more than 43 million people currently living in this region. Plain Language Summary: Climate models project significant drying for the Caribbean as a consequence of increased anthropogenic greenhouse‐gas concentrations. Between 2013 and 2016, virtually, the entire region experienced a Pan‐Caribbean drought, which was unprecedented since at least 1950. We find that human‐caused warming contributed to 15–17% of drought severity by increasing evapotranspiration rates and accounted for 7% of land area under drought across the Caribbean. Our results therefore suggest that anthropogenic warming has already increased drought risk in the Caribbean. Key Points: In 2013–2016, the Caribbean experienced its worst drought since 1950, which we named the Pan‐Caribbean drought Enhanced evaporative demand due to anthropogenic warming contributed to 15–17% of Pan‐Caribbean drought severity Anthropogenic climate change has likely already enhanced drought risk in the Caribbean